CPhill

avatar
Nombre de usuarioCPhill
Puntuación111435
Membership
Stats
Preguntas 53
Respuestas 35267

 #3
avatar+111435 
+1

Here's the solution ....

 

Note that we should have this equation

 

9x + 17y  =  541           which we can manipulate as follows

 

9x  =     541  - 17y

 

x  =        541  - 17y

             ________

                     9

 

x  =  541   -  (18 - 1)y

       _____________

                   9

 

x  =  541 + y                18y

       _______     -        ____

             9                      9

 

x  =  540  + 1 +  y                18y

        ___________   -         ____

                   9                         9

 

x =  540           1 + y             18y

      ___   +       _____  -       ___

        9                  9                 9

 

Note that the first and last terms will always be divisible by 9

 

And.....the middle term will be divisible by 9  when y  =  8, 17  or 26

 

 

So   we have the following possibilities for x

 

x  =  541 - 17(8)        =      45

        _________   

               9

 

x =   541 - 17*17    =    28

        __________

                9

 

x =   541  -   17*26      =   11

        ____________

                  9

 

Note   if y =  35,we get the next multiple of 9...but  x  = -6 if this is so....    so....these are the only possible solutions

 

So....the solutions  (x, y)   = ( 11,26)  (28, 17)  (45, 8)

 

Just add these coordinates and you will get your answer, CU

 

 

cool cool cool

22 jun. 2019
 #1
avatar+111435 
+2

Using the change-of base theorem  we have

 

log (3x + 4)             log (3x + 4)         log (3x + 4)               (1/2)log(3x + 4)

_________    =      __________  =   ______________=    ____________    (1)

log 4                          log 2^2                2 log 2                         log 2

 

log ( 7x + 8)        log(7x + 8)           log (7x + 8)                (1/3)log(7x + 8)

_________   =  __________  =  _____________ =        _____________   (2)

log 8                    log 2^3                  3 log 2                           log 2

 

The arithmetic difference must  be   (2) - (1)  =

    

(1/3) log (7x + 8) - (1/2)log(3x + 4)

__________________________

                  log 2

 

This implies that

 

log (x + 2)               (1/3)log(7x + 8) - (1/2)log (3x + 4)              (1/2)log(3x + 4)

________    +        ____________________________   =    ______________

  log   2                                  log 2                                                log 2

 

 

 

;log (x + 2)  +  (1/3)log(7x + 8) - (1/2)log(3x + 4)  =  (1/2)log(3x + 4)

 

log (x + 2) + (1/3)log(7x + 8)    =   log(3x + 4)

 

3 log( x + 2)  + log(7x + 8)  = 3log(3x + 4)

 

log ( x + 2)^3 + log(7x + 8)    =  log (3x + 4)^3

 

log  [ (x + 2)^3 * (7x + 8)]  = log(3x + 4)^3

 

Which implies that

 

(x + 2)^3 (7x + 8)  = (3x + 4)^3

 

(x^3 + 3x^2*2 + 3x*4 + 2^3) (7x + 8)   =  (3x)^3  + 3* (3x)^2*4 + 3* 3x*4^2 + 4^3

 

( x^3 + 6x^2 + 12x + 8)(7x + 8)  =  27x^3 + 108x^2 + 144x + 64

 

7 x^4 + 50 x^3 + 132 x^2 + 152 x + 64  =  27x^3 + 108x^2 + 144x + 64

 

7x^4 + 23x^3 + 24x^2 + 8x  = 0

 

x (7x^3 + 23x^2 + 24x + 8)  = 0

 

x = 0 is one solution

 

7x^3 + 23x^2 + 24x + 8  = 0

 

Using the Rational zeroes theorem, I see that x = -1 is also another solution

 

So....we can use synthetic division to find the residual polynomial

 

 

-1  [  7     23     24      8   ]

                -7     -16    -8

       ________________

        7     16       8       0

 

 

The   remaining polynomial is     7x^2  + 16x + 8

 

Using the Quadratic Formula  

 

x =    -16 ±√ [ 16^2  - 4(7)(8) ]      =          -16  ±√ 32      =      -16 ± 4√2    =     -8 ±2√2

        ____________________                __________          _________        _______

                   2 *7                                            14                          14                       7

 

The solution  -8 - 2√2

                     _______  ≈  -1.55       which makes two of the original logs undefined  

                           7

 

So

 

 

x  =   -8 + 2 √2

        _________  ≈  -.74

               7

 

a =  8   b =  2    c  = 2   d  = 7

 

And their sum  =    19

 

 

cool cool cool     

21 jun. 2019